Assessment of quality indicators for emergency departments: First results using a modified QUALIFY approach with subsequent interprofessional expert discussion Bewertung von Qualitätsindikatoren für die Notaufnahme: Erstmalige Anwendung eines modifizierten QUALIFY-Ansatzes mit nachfolgender interprofessioneller Expertendiskussion - Kulla, M.; Goertler, M.; Somasundaram, R.; Walcher, F.; Greiner, F.; Lefering, R.; Wrede, C.; Rubak, K.; Hörster, A.; Baacke, M.; Erdmann, B.; Dormann, Harald; et al. (Notfall und Rettungsmedizin, 2016)
Background: Approximately 22 million patients are treated annually in German emergency departments (ED). However, few quality indicators have been evaluated for use in EDs in Germany. Here we describe for the first time the assessment of a panel of internationally established quality indicators and their value for German EDs by using the standardised QUALIFY method, followed by an open, interprofessional discussion. Materials and methods: Based on a systematic literature review 35 potentially eligible quality indicators were chosen. First, their strengths and limitations were evaluated using the QUALIFY method by a group of 14 experts. In a second step, the same experts discussed the potential indicators in an open discussion round. Descriptive statistics were performed to report the results of the QUALIFY process and the results of the open discussion. Both approaches were compared by calculating Cronbach’s α. The results were reported in a standardised quality indicator registry. Results: The interprofessional working group of experts rated 20 of 35 international published quality indicators being of value for the use in German EDs; 11 indicators were rated less valuable for reasons of e. g. potentially adverse effects or problems regarding the implementation process. The results of the anonymous and standardised QUALIFY process matched the results of the open discussion in 89 % (Cronbach’s α = 0.865). A relevant modification of 20 % (7/35) and a precise definition of 16 of the 35 quality indicators were additional results of the discussion process. Conclusion: The QUALIFY method allows for rapid and structured identification of the potential of published indicators without the bias of mutual influence of the expert group members. Although more time consuming, the open discussion process produces additional results like precise and well phrased quality indicators for the specific setting. The two methods show a high grade of congruence. It is important to state that the reported quality indicators need to be evaluated for their validity, specificity, discrimination capability etc. before they are used in benchmarking projects.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Benchmarking; Emergency medicine; Methods evaluation; QUALIFY method; Registries